State-building under foreign occupation: the case of Iraq, 2003-2008 - Jalal, Abdul Wahed; Abdel Salam, El Fatih Abdullahi (IIUM Press, International Islamic University Malaysia, 2017)
The aim of this book is to analyze the political system of Iraq (2003-2008) which emerged under the foreign occupation. Power-sharing (consociational) model which emphasizes the role of the political elites is used as the most appropriate approach in order to book post-Saddam Iraq. The book identifies factors that are conducive to cooperative behavior of domestic elite. These factors are: nature of social cleavages, size of various ethnic groups and segmental isolation. Elite behavior is examined in terms of a grand coalition, segmental autonomy, proportional representation and mutual veto. The book shows that Iraq’s political elites have been confrontational and non-cooperative which normally leads to political instability. However, during this period the country has achieved some kind of power sharing arrangement and moderate economic development. This has been possible due to external factors, such as the presence of United States and United Kingdom forces which has made unilateral decisions and passed laws that domestic political elites have not been able to agree upon. This has enabled the country to function rather smoothly in the post-Saddam Iraq. The book is based upon data collected through personal interviews with political elites, documents published by the United Nations, International Monetary Fund, books, local newspapers, journals, and magazines.